2018
DOI: 10.1038/s41366-018-0149-3
|View full text |Cite
|
Sign up to set email alerts
|

Maternal pre-pregnancy obesity and health care utilization and costs in the offspring

Abstract: Background/objective The association between maternal pre-pregnancy obesity and adverse child health outcomes is well described, but there are few data on the relationship with offspring health service use. We examined the influence of maternal pre-pregnancy obesity on offspring health care utilization and costs over the first 18 years of life. Methods This was a population-based retrospective cohort study of children (n = 35,090) born between 1989 and 1993 and their mothers, who were identified using the Nova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…To our knowledge, none were specifically in low-risk people. 5,[13][14][15][16][17] For example, analysis of electronic data records of 13,422 pregnant people from a U.S. group-practice health maintenance organization from 2000 to 2004 showed that a higher-than-normal BMI was associated with a prolonged length of hospital stay for delivery (4.060.1 days and 4.460.1 days for those with BMIs in the obese and extremely obese ranges compared with 3.660.1 days for those with BMIs in the normal range), with the bulk of increase related to higher rates of cesarean delivery. 5 However, the difference remained significant after correction for mode of delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, none were specifically in low-risk people. 5,[13][14][15][16][17] For example, analysis of electronic data records of 13,422 pregnant people from a U.S. group-practice health maintenance organization from 2000 to 2004 showed that a higher-than-normal BMI was associated with a prolonged length of hospital stay for delivery (4.060.1 days and 4.460.1 days for those with BMIs in the obese and extremely obese ranges compared with 3.660.1 days for those with BMIs in the normal range), with the bulk of increase related to higher rates of cesarean delivery. 5 However, the difference remained significant after correction for mode of delivery.…”
Section: Discussionmentioning
confidence: 99%
“…14,[16][17][18][19][20] A cross-sectional analysis of 16,262 patients from the 2000 Medical Expenditure Panel Survey in the United States demonstrated that excess costs among adults with morbid obesity resulted from greater expenditures for office-based visits, outpatient and in-patient hospital care, and prescription drugs. Moreover, overweight and obese BMI status in pregnant people were associated with increased costs of care for the newborn and child, compared with those BMIs in the normal range, 14,18 and modeling estimates of the average incremental costs associated with pregnancy and birth were more than $18,290. 19 We demonstrate a robust association between maternal BMI and increased utilization of health care resources in low-risk pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…We looked at the longitudinal variation to see if the numbers of NIPT and IPD over time align with or exceeds the changes in the number of new high-risk pregnancies with advanced maternal age. Analytic cohort included pregnant women with one or more records of high-risk pregnancy (ICD-10-CM O09.x or ICD-9-CM V23.x) between January 2012 and December 2018 24–30. Eligible subjects were 35 years old or older at the first date of the high-risk pregnancy diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Besides increased perinatal complications, maternal obesity also leads to increased morbidity in the children of obese mothers [ 6 , 7 , 8 ]. In particular, maternal obesity is a risk factor for compromised cognitive development, metabolic syndrome, and even childhood cancers [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%